Novel fusion cells derived from tumor cells expressing the heterologous α-galactose epitope and dendritic cells effectively target cancer. Issue 7 (8th February 2019) - Mo, Fengzhen; Xue, Dabing; Duan, Siliang; Liu, Aiqun; Yang, Xiaomei; Hou, Xiaoqiong; Lu, Xiaoling
Highlights: Using one antigens (α-Gal) for the first time to prepare tumor/DC fusion cells. Tumor (Gal + )/DC fusion cells were demonstrated as a novel strategy against cancer. Abstract: Tumor cells/dendritic cells (DCs) fusion cells (tumor/DC) represent a promising immunotherapeutic strategy but are still under performed in clinical trials for cancer treatment. To further boost their anticancer efficacy, here we developed a novel design for fusing dendritic cells with MDA-MB-231 cells expressing the heterologous α-galactose (α-gal) epitope and assessed its anticancer activities both in vitro and in vivo. The high expression of α-gal in MDA-MB-231 (Gal + )/DC correlated with enhanced DC activation. When applied to T cells, MDA-MB-231 (Gal + )/DC significantly stimulated T-cell proliferation and activation, promoted productions of cytokines IL-2 and IFN-γ, and enhanced T-cell-mediated cytotoxicity against MDA-MB-231 cells. MDA-MB-231 (Gal + )/DC inhibited proliferation and promoted apoptosis of tumor cells in vivo, prolonged mouse survival, and significantly boosted anticancer immunity by increasing CD4 + and CD8 + T cells systemically and elevating serum levels of cytokines and IgG. These results suggested that fusing dendritic cells with tumor cells expressing the heterologous α-gal epitope provides a novel therapeutic strategy for cancer treatment.